The impact of online harassment via social media to self-esteem among youth / Nur Shazana Abdul Rani … [et al.] - Abdul Rani, Nur Shazana; Ab. Hadi, Siti Nur Izyandiyana; Abd Aziz, Siti Hajar; Abdul Wahab, Shafezah (Faculty of Communication & Media Studies, 2024)
The pervasive use of social media among teenagers and youth has surged in recent years, bringing with it a concerning rise in online harassment. This study investigates the impact of online harassment on the mental health and self-esteem of youth. Employing a qualitative approach, data and perspectives were gathered from 28 participants aged 19 to 29, representing both genders. The findings reveal widespread awareness of online harassment among respondents, with many reporting personal experiences of being targeted. Importantly, the study underscores the detrimental effects of social media harassment on individuals' self esteem and mental well-being. As social media continues to play an integral role in modern communication, it is imperative for users to exercise mindfulness and empathy, fostering a digital environment free from harm and intimidation.